1976
DOI: 10.1002/1097-0142(197608)38:2<633::aid-cncr2820380203>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of Wilms' tumor. Results of the national Wilms' tumor study

Abstract: The National Wilms' Tumor Study, initiated in 1969, tested competing treatment strategems for patients with tumors ranging from Group (Gp) I (tumors confined to the kidney and totally removed) to Gp IV (remote metastases present at diagnosis). Three hundred and fifty‐nine of 606 registered patients were randomized in the trial. Gp I patients under 2 years of age fared well whether postoperative radiation therapy (RT) was or was not added to 15 months' maintenance actinomycin D (AMD). Their prognosis was better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
125
0
10

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 416 publications
(139 citation statements)
references
References 19 publications
4
125
0
10
Order By: Relevance
“…8 D'Angio et al noted equal incidence on both sides and bilateral tumours in 5%. 7 We found equal incidence on both side similar to that of D' Angio et al finding 7 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…8 D'Angio et al noted equal incidence on both sides and bilateral tumours in 5%. 7 We found equal incidence on both side similar to that of D' Angio et al finding 7 …”
Section: Discussionsupporting
confidence: 89%
“…5 Howard et al reported 75% incidence between the age of 1 and 5 years, and 90% below the age of 7 years. 1 We had 92% of cases below the age of 7 years which similar to that of D'Angio, 7 Harward et al 1 Incidence for Wilms' tumor was almost equal (0.97:1) in series of Bennington. 4 Bernard 5 reported M:F ratio of 1:1.7.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There is a variable degree of penetration in cases involving familial Wilms' tumor. This phenomenon has been previously reported in twins [5,9], but has been reported in only one of two monozygote twins and in a younger brother [6]. There is a much higher incidence rate of bilateral renal tumors in familial cases.…”
Section: Discussionmentioning
confidence: 51%
“…The conservative resection protocol adapted for cases of bilateral Wilms' tumor according to NWTS III should be followed, but with special reservation which has been reported by Laberge et al [7]. It is well known that results of Wilms' tumor treatment are among the best in infant neoplasms [9]; the higher cure rate is due mainly to improved surgical procedures, as well as the sensitivity of WT to chemotherapeutic agents and radiotherapy. BWT usually has a favorable histology in younger patients.…”
Section: Discussionmentioning
confidence: 99%